Hyperfine structure constants for singly ionized manganese (Mn II) using Fourier transform spectroscopy - Townley-Smith,K; Nave,G; Pickering,JC; Blackwell-Whitehead,RJ (Monthly Notices of the Royal Astronomical Society, 2016)
We expand on the comprehensive study of hyperfine structure (HFS) in Mn II conducted byHolt et al. (1999) by verifying hyperfine magnetic dipole constants (A) for 20 levels previouslymeasured by Holt et al. (1999) and deriving A constants for 47 previously unstudied levels. TheHFS patterns were measured in archival spectra from Fourier transform (FT) spectrometers atImperial College London and the National Institute of Standards and Technology. Analysis ofthe FT spectra was carried out in XGREMLIN. Our A constant for the ground level has a loweruncertainty by a factor of 6 than that of Blackwell-Whitehead et al.